Applied Fuzzy Arithmetic An Introduction with Engineering Applications - Hanss, Michael (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Applied Fuzzy Arithmetic provides a well-structured compendium that offers both a deeper knowledge about the theory of fuzzy arithmetic and an extensive view on its applications in the engineering sciences, making it a resource for students, researchers, and practical engineers. The first part of the book gives an introduction to the theory of fuzzy arithmetic, which aims to present the subject in a well-organized and comprehensible form. The derivation of fuzzy arithmetic from the original fuzzy set theory and its evolution towards a successful implementation is presented with existing formulations of fuzzy arithmetic included and integrated in the overall context. The second part of the book presents a diversified exposition of the application of fuzzy arithmetic, addressing different areas of the engineering sciences, such as mechanical, geotechnical, biomedical, and control engineering.